BRONCHIAL ASTHMA IN CHILDREN: CAUSES, CLINICAL MANIFESTATIONS AND TREATMENT APPROACHES (International journal of medical sciences, 2026)
Bronchial asthma is one of the most common chronic respiratory diseases in childhood and represents a major public health concern worldwide. According to the World Health Organization and the Global Initiative for Asthma (GINA), millions of children suffer from asthma, and its prevalence continues to increase due to environmental and genetic factors. This article examines the causes, risk factors, clinical manifestations, diagnostic features, and modern approaches to the treatment and control of bronchial asthma in children. Special attention is paid to genetic predisposition, environmental triggers, allergens, and respiratory infections that contribute to the development of asthma. Evidence-based treatment strategies, including pharmacological therapy, preventive measures, and long-term disease control, are also analyzed. The study highlights the importance of early diagnosis, proper management, and continuous monitoring in improving the quality of life of children with asthma and reducing complications.